A low-power low-noise CMOS bio-potential amplifier for multi-channel neural recording with active DC-rejection and current sharing. (January 2019) - Gharaei Jomehei, Maryam; Sheikhaei, Samad
Abstract: A low-power and low-noise bioamplifier for multichannel electrode arrays (MEA) is presented. Reduction in area and power is achieved (1) by means of active-integration using a small capacitor, (2) implementation of a high-pass filter without using large DC-blocking capacitors, and (3) by sharing the common parts of bioamplifiers of different channels. This bioamplifier, as the main building block of a neural recording system, has been designed to record neural signals, amplify them, filter out the unwanted signals, and extract the action potentials. Theoretical analysis on noise specification, crosstalk between the channels due to sharing parts, and power reduction has been presented and a design trade-off is achieved. Following the theoretical analysis, a 4-channel bioamplifier has been designed and simulated in 0.18 μm CMOS technology, in total layout area of 0.0976 mm 2 and the current consumption of 3.2 μA per channel from ±1.2 V power supply. Based on post-layout simulation results, the power and noise specifications of the proposed design are comparable with the best specifications reported to date based on noise efficiency factor (NEF). The bioamplifier achieves a mid-band gain of 60 dB and a -3 dB bandwidth from 100 Hz to 10.2 kHz. The input-referred noise is 3.87μV rms corresponding to a NEF of 2.65, for the mentioned -3 dB bandwidth.